Pengaruh CAR, NPF, DER terhadap Pembiayaan Murabahah dengan DPK sebagai Variabel Moderating - Agust Setiawan; Saiful Anwar (Prodi Perbankan Syariah FAI UMT, 2022)
This research is motivated by the development of murabahah financing which has increased during the Covid-19 pandemic. The purpose of this study was to determine the effect of CAR, NPF and DER on Murabahah Financing with TPF as a Moderating Variable. This research uses quantitative research using multiple linear regression analysis. The data used is secondary data, with the population of Islamic Commercial Banks in Indonesia in 2015-2020.The sampling technique used purposive sampling, and obtained a sample of 11 Islamic Commercial Banks that meet the criteria. The analytical tool used is Eviews 9. The results showed the results of the t test that CAR had a significant positive effect on Murabahah Financing, NPF and DER had no effect on Murabahah Financing.The results of the MRA test show that TPF is able to moderate the effect of CAR, NPF on Murabahah Financing, while TPF is not able to moderate the effect of DER on Murabahah Financing.